AGROBACTERIUM-MEDIATED GENETIC TRANSFORMATION OF SEAWEED Kappaphycus alvarezii USING Gα GENE AND CALLUS CULTURES - Erina Sulistiani; Suharsono Suharsono; Ence Darmo Jaya Supena; Miftahudin Miftahudin (SEAMEO BIOTROP, 2019)
Cottonii seaweed (Kappaphycus alvarezii Doty) is one of the most important commercial sources of carrageenan, which is widely used in the pharmaceutical and food industries. A major problem in the cultivation of this seaweed is ice-ice disease, which is caused by extreme changes in environmental conditions such as temperature and seawater salinity. Gene transformation to produce transgenic Kappaphycus lines that are tolerant to environmental stress is a potential solution to this problem. The Gα gene, which encodes the heterotrimeric G-protein alpha subunit, plays an important role in tolerance to biotic and abiotic environmental stress. This study aimed to: (a) introduce the Gα gene into the callus cells of K. alvarezii and regenerate transformed callus cells into transgenic plantlets; and (b) determine the appropriate concentration of acetosyringone and Agrobacterium tumefaciens strain for successful gene transfer into the callus of K. alvarezii. The callus cells of K. alvarezii were transformed using Agrobacterium tumefaciens strains LBA4404 and EHA105 carrying the expression vector pGWB502-Gα under the control of the CaMV-35S promoter. The calli and A. tumefaciens were co-cultivated in different concentrations of acetosyringone (20, 40, and 60 mg/L). The regeneration of transformed callus cells into transgenic plantlets was successfully achieved using the somatic embryogenesis technique. The results showed that the highest percentage of putative transgenic micropropagule formation occurred at acetosyringone concentrations of 20–40 mg/L. Polymerase chain reaction (PCR) analysis of twenty regenerated plantlets indicated that the Gα gene was successfully introduced into the genomic DNA of all samples. The highest transformation efficiency was obtained from the 20–40 mg/L acetosyringone co-cultivation treatment (22–28%). The transformation efficiency produced by Agrobacterium tumefaciens EHA105 (23%) was not significantly different from that produced using strain LBA4404 (15%).